(untitled) (El Hilo de la Fabula, 2023)
Grace Nichols, Guyanese poet living in the United Kingdom since 1977, is especially recognised for her three first books: I is a Long-Memoried Woman (1983, awarded the Commonwealth Poetry Prize), The Fat Black Woman’s Poems (1984), and Lazy Thoughts of a Lazy Woman (1989), in which critics see a certain continuity. One of the central critical approaches focuses in how erotism is present in her work. Thus, from a feminist perspective, Nichols has been praised and criticised for the prominent place the body and sexuality has in the construction of her poetic persona (Escudero, 2000; Harding, 2007; Scalon, 1998). Female sexuality and the vital role Nichols gives to the body have been read in consonance with «écriture féminine», using the theories by Hélène Cixous, Luce Irigaray, Julia Kristeva (Griffin, 1993; Webhofer, 1996; DeCaires Narain, 2004). The aim of this essay is to propose another possible viewpoint to think the presence of erotism in Nichol’s work: as a way of constructing a metapoetics in which sensuality and creation merge. Erotism would not be, then, a weapon Nichols holds as a «poelitics» (Chancy, 1997; Bringa López, 2003), but a declaration about how to understand the act of creation. For this purpose, based on the vision of eroticism defined by Georges Bataille (1985, [1957]), Octavio Paz’s (1995) connection between poetry and erotism, and the use of sexuality as a creative source defended by Audre Lorde (1984), three poems from Lazy Thoughts of a Lazy Woman: «On Poems and Crotches», «My Black Triangle» and «With apologies to Hamlet» will be analysed.